A decade of leafminer invasion in China: lessons learned. Issue 9 (2nd June 2017) - Gao, Yulin; Reitz, Stuart; Xing, Zhenlong; Ferguson, Scott; Lei, Zhongren
Abstract: Liriomyza trifolii (Burgess) is a highly invasive species that has become established in agricultural and ornamental crops throughout the world. L. trifolii was first recorded in China in 2005 in Guangdong Province. Subsequently, its known distribution in China has rapidly expanded to another 11 provinces (Zhejiang, Jiangsu, Shanghai, Fujian, Guangxi, Shandong, Hainan, Hebei, Henan, Hubei and Anhui), where it is currently causing considerable damage and economic losses. Experimental research and field surveys have contributed to our understanding of the ecology of L. trifolii and particularly the process of invasion and its interactions with other established, exotic Liriomyza leafminer species. A number of factors have contributed to the successful establishment of L. trifolii and displacement of interspecific competitors. In China, L. trifolii has become a particularly devastating pest in areas with intensive farming with extensive monocultures and a reliance on insecticide use. Integrated pest management incorporating judicious applications of insecticide combined with biological and cultural controls is likely to provide the best long‐term management strategy for L. trifolii . We provide information regarding 10 years of L. trifolii invasion in China and discuss areas of future research to enhance our overall understanding of the biology and ecology of L. trifolii and to improve management programmes for this widespread invasive insect pest. © 2017 Society of Chemical Industry